(untitled) (JEELT : JOURNAL OF EDUCATION AND ENGLISH LANGUAGE TEACHING, 2023)
This research aimed to find out what strategies students used to master vocabulary. The subjects of this research were eighth grade C students at SMP Negeri 19 Pontianak City. The sample was selected by purposive sampling. Researcher used a quantitative data approach. To collect data, researcher used a close-ended questionnaire. The data from the closed-ended questionnaire were metacognitive strategies, social strategies, memory strategies, determination strategies and cognitive strategies. The results of the data analysis carried out show that metacognitive strategies were the ones most used by students when studying English and cognitive strategies were the strategies least used by students